The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5468/ogs.2017.60.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence factors and reproductive outcomes of laparoscopic myomectomy and minilaparotomic myomectomy for uterine leiomyomas

Abstract: ObjectiveThe aim of this study was to determine recurrence factors and reproductive outcomes of laparoscopic myomectomy (LM) and minilaparotomic myomectomy (MM) for treating uterine leiomyomas.MethodsBetween 2007 and 2013, 160 patients underwent myomectomy, including 122 who underwent LM and 38 who underwent MM. Patients were followed up for recurrence based on pelvic ultrasound exams. Only patients who were followed up for a minimum of two years were selected for this retrospective study. Pregnancy rate, deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Clinically, pre-treatment with Gn RH-a before surgery can be used for patients with anemia or excessive fibroid volumes to correct anemia or reduce fibroid volume, thus reducing the occurrence of surgical complications ( 28 ). However, other studies have recently shown that treatment with Gn RH-a before fibroid resection leads to an increased risk of recurrence in patients, which may be because Gn RH-a reduces the volume of preoperative fibroids and affects the identification of small fibroids during surgery ( 31 , 32 ) and leads to incomplete intraoperative fibroid resection. This suggests that we should be more meticulous in preoperative and intraoperative color Doppler ultrasonography, strictly control the surgical indications, and select an appropriate surgical plan accordingly to improve the safety and effectiveness of surgery, to reduce the possibility of postoperative recurrence ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, pre-treatment with Gn RH-a before surgery can be used for patients with anemia or excessive fibroid volumes to correct anemia or reduce fibroid volume, thus reducing the occurrence of surgical complications ( 28 ). However, other studies have recently shown that treatment with Gn RH-a before fibroid resection leads to an increased risk of recurrence in patients, which may be because Gn RH-a reduces the volume of preoperative fibroids and affects the identification of small fibroids during surgery ( 31 , 32 ) and leads to incomplete intraoperative fibroid resection. This suggests that we should be more meticulous in preoperative and intraoperative color Doppler ultrasonography, strictly control the surgical indications, and select an appropriate surgical plan accordingly to improve the safety and effectiveness of surgery, to reduce the possibility of postoperative recurrence ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy is the most common surgical modality used by gynecologists [ 10 ]. Most scholars believe that patients with fibroids larger than 10 cm in diameter, more than 4 in number, and close to submucosal fibroids, as well as cervical fibroids, are relative contraindications to laparoscopic surgery, causing difficulty and even complications [ 38 , 39 , 40 ]. Robot-assisted systems have their own unique advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine fibroids are common benign tumors of the female reproductive system, mostly in women of childbearing age, with an incidence of up to 40% [ 1 ]. It is mainly caused by the proliferation of smooth muscle cells, formed by fibrous connective tissue, and, can cause irregular vaginal bleeding in female patients, menorrhagia, pelvic pain, frequent urination, constipation, abortion, and infertility and other symptoms.…”
Section: Introductionmentioning
confidence: 99%